Thrombus Aspiration in ST-Segment–Elevation Myocardial Infarction: An Individual Patient Meta-Analysis. Issue 2 (10th January 2017) - Jolly, Sanjit S.; James, Stefan; Džavík, Vladimír; Cairns, John A.; Mahmoud, Karim D.; Zijlstra, Felix; Yusuf, Salim; Olivecrona, Goran K.; Renlund, Henrik; Gao, Peggy; Lagerqvist, Bo; Alazzoni, Ashraf; et al.
Abstract : Background: Thrombus aspiration during percutaneous coronary intervention (PCI) for the treatment of ST-segment–elevation myocardial infarction (STEMI) has been widely used; however, recent trials have questioned its value and safety. In this meta-analysis, we, the trial investigators, aimed to pool the individual patient data from these trials to determine the benefits and risks of thrombus aspiration during PCI in patients with ST-segment–elevation myocardial infarction. Methods: Included were large (n≥1000), randomized, controlled trials comparing manual thrombectomy and PCI alone in patients with ST-segment–elevation myocardial infarction. Individual patient data were provided by the leadership of each trial. The prespecified primary efficacy outcome was cardiovascular mortality within 30 days, and the primary safety outcome was stroke or transient ischemic attack within 30 days. Results: The 3 eligible randomized trials (TAPAS [Thrombus Aspiration During Percutaneous Coronary Intervention in Acute Myocardial Infarction], TASTE [Thrombus Aspiration in ST-Elevation Myocardial Infarction in Scandinavia], and TOTAL [Trial of Routine Aspiration Thrombectomy With PCI Versus PCI Alone in Patients With STEMI]) enrolled 19 047 patients, of whom 18 306 underwent PCI and were included in the primary analysis. Cardiovascular death at 30 days occurred in 221 of 9155 patients (2.4%) randomized to thrombus aspiration and 262 of 9151 (2.9%) randomized to PCI alone (hazard ratio, 0.84; 95% confidence interval, 0.70–1.01; P =0.06). Stroke or transient ischemic attack occurred in 66 (0.8%) randomized to thrombus aspiration and 46 (0.5%) randomized to PCI alone (odds ratio, 1.43; 95% confidence interval, 0.98–2.10; P =0.06). There were no significant differences in recurrent myocardial infarction, stent thrombosis, heart failure, or target vessel revascularization. In the subgroup with high thrombus burden (TIMI [Thrombolysis in Myocardial Infarction] thrombus grade ≥3), thrombus aspiration was associated with fewer cardiovascular deaths (170 [2.5%] versus 205 [3.1%]; hazard ratio, 0.80; 95% confidence interval, 0.65–0.98; P =0.03) and with more strokes or transient ischemic attacks (55 [0.9%] versus 34 [0.5%]; odds ratio, 1.56; 95% confidence interval, 1.02–2.42, P =0.04). However, the interaction P values were 0.32 and 0.34, respectively. Conclusions: Routine thrombus aspiration during PCI for ST-segment–elevation myocardial infarction did not improve clinical outcomes. In the high thrombus burden group, the trends toward reduced cardiovascular death and increased stroke or transient ischemic attack provide a rationale for future trials of improved thrombus aspiration technologies in this high-risk subgroup. Clinical Trial Registration: URLs:http://www.ClinicalTrials.gov http://www.crd.york.ac.uk/prospero/ . Unique identifiers: NCT02552407 and CRD42015025936. Abstract : Supplemental Digital Content is available in the text.